Some naturally occurring and synthetic food components, furocoumarins and ultraviolet radiation (International Agency for Research on Cancer, 1986)
Evaluates the carcinogenic risk to humans posed by exposure to some Naturally Occurring and Synthetic food components, Furocoumarins and Ultraviolet Radiation.
IARC monographs on the evaluation of carcinogenic risk of chemicals to human ; Vol. 40
Keywords: chemie, klinická chemie; Carcinogens; onkologie; karcinogeny